2018
DOI: 10.18535/ijsrm/v6i10.el05
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cultural Factors on Pupil’s Transition from Primary to Secondary Schools in Laikipia West Sub-County, Kenya

Abstract: From 2017, the government of Kenya aimed at attaining 100 percent transition rate of pupils from primary to secondary schools. In Laikipia West Sub-County whose primary schools are focused by the study, transition from primary to secondary schools averaged at 54.9% from 2008 to 2015. Cultural factors are highlighted in literature as to undermine transition of pupils from primary to secondary schools. The purpose of the study was to determine the extent to which cultural factors influence pupils’ transition fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…This left the staff to make personal initiatives on how and where to get the records management policy manuals. The same sentiments were also shared by Mwangi et al (2017) who pointed that one of the key hinderance of records management in Laikipia county was related to unavailability of policy manuals to update the staff on diverse policies. The available manuals were related to County Acts as stipulated by the parliament.…”
Section: Descriptive Statistics Of Records Management Policiesmentioning
confidence: 73%
“…This left the staff to make personal initiatives on how and where to get the records management policy manuals. The same sentiments were also shared by Mwangi et al (2017) who pointed that one of the key hinderance of records management in Laikipia county was related to unavailability of policy manuals to update the staff on diverse policies. The available manuals were related to County Acts as stipulated by the parliament.…”
Section: Descriptive Statistics Of Records Management Policiesmentioning
confidence: 73%
“…Some studies have been done on the use of graffiti in the classroom. In a study undertaken by Mwangi (2012), the focus was on the examination of graffiti writing and its possible implications for English language education in selected schools within the larger Laikipia East District in Kenya. This research aimed to explore the many varieties of graffiti present in educational institutions, while also analysing the communication tactics used in graffiti writing, aesthetic norms, symbolism, and visual metaphor.…”
Section: The Graffiti Wallmentioning
confidence: 99%
“…Pastoralists occupy the driest downstream parts of the basin, where shortage of pasture and water scarcity occur, especially during the dry season (Notter et al, 2007;Mati et al, 2005). Due to land use changes and expansion of cultivation, livestock herd sizes have been reducing especially among the pastoralists (Mwangi et al, 2020), while natural grasslands have become denudated. As a result, the UENB faces numerous conflicts.…”
Section: Constraints Faced By Communities Normallymentioning
confidence: 99%
“…The fact that droughts lead to conflicts in the UENB has been noted in other studies. Mwangi et al (2020) observed that in semi-arid zones, intra and inter communal conflicts occur during drought periods and pastoralists compete for scarce resources mainly grass and water for their animals. This happens in areas shared by farmers and pastoralist, particularly when livestock encroach on farmlands.…”
Section: Drought Impacts On Community Livelihoodsmentioning
confidence: 99%